A23 Population level diversification of hepatitis C viral strains over time among people who inject drugs in Baltimore, MD - Hackman, J (Virus Evol, 2019)
Hepatitis C virus (HCV) infection occurs in 30–90 per cent of people who inject drugs (PWID). Although cure rates can exceed 95 per cent, treatment access is limited and approximately 400,000 people die each year due to complications of chronic infection. A temporal analysis of cluster networks among PWID can be used to inform strategies to interdict transmission. In Baltimore, PWID have been recruited for The AIDS Linked to the IntraVenous Experience (ALIVE) cohort. A demographic questionnaire was administered and recorded for baseline and recent participants. Viral RNA underwent PCR with primers targeting the core and envelope-1 protein (CE1) and sequenced via Sanger sequencing. Sequences with > 400 bp reads and Q-scores >370 were used for downstream analysis resulting in 322 ALIVE baseline participants (1988–9) and 548 recently diagnosed subjects enrolled approximately two decades later (2005–16). Cluster networks were rendered with a threshold of 4 per cent in MicrobeTRACE, and statistical analyses were performed in R Studio. Of the 1988–9 subjects, the majority (259/317, 81.7%) were a part of cluster. There were nine clusters and fifty-eight singletons, with two large clusters containing most sequences of genotype 1a (73.5%). Two decades later, a minority of recently diagnosed individuals (235/512, 44.1%) were part of a cluster. There were seventeen clusters with 286 singletons with two large clusters containing 1a genotype individuals (21.5%). Additional clustering was done by parsing the two datasets by subtype 1a (n = 714) and 1b (n = 151). The genotype 1a network demonstrates a majority, 65.8 per cent, of participants in clusters. Moreover, two large clusters can be observed with baseline participants towards the center and recent participants on the outskirts indicative of high linkage at baseline. The genotype 1b network produced a single large cluster but subclusters were observed. The sequences between the two time points co-mingled but subclusters were also observed. Interestingly, the two large clusters from 1988 to 1989 were still evident in the 2005–16 viral sequences. We observed greater cluster diversity in more recently diagnosed individuals, indicative of a less connected network of individuals sharing transmission risk, though major viral strains did persist over time in this cohort.